Analisis Kondisi Sosial-Ekonomi dan Potensi Pemberdayaan Masyarakat di Desa Aek Najaji Kota Padangsidimpuan: Penelitian - Ali Nurdin Siregar; Nurmaini Ginting; Nursahara (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Village community empowerment is key to improving welfare and addressing socio-economic challenges. Aek Najaji Village in Padangsidimpuan Batunadua District has potentials and challenges that require analysis to design an appropriate empowerment model. This study analyzes the village’s socio-economic conditions, identifies potentials and challenges, and formulates an empowerment model suited to its characteristics. Using a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews with 29 informants, FGDs, and documentation (October 2024–January 2025). Data analysis employed the Miles and Huberman interactive model with data triangulation. Findings indicate strong social cohesion (Social Capital Index 7.8/10) and a community participation rate of 72%. The economy is dominated by the informal sector: farmers (40%), farm laborers (25%), and construction workers (20%). Potentials include agricultural natural resources, strong social capital (85% community participation in mutual cooperation), and high enthusiasm for empowerment programs. Key challenges are limited market access, low economic diversification, and minimal youth involvement. The recommended model is a Social Capital-Based Participatory Empowerment approach focusing on capacity building, economic diversification, and strengthening village institutions.